EFEKTIVITAS PENDIDIKAN DAN PELATIHAN JARAK JAUH GURU MATEMATIKA MADRASAH ALIYAH DI BALAI DIKLAT KEAGAMAAN PALEMBANG - Iwan Sugianto (Conciencia, 2015)
Increased professionalism of employees or teachers can through education and training (training). Religious Training Center (BDK) Palembang is one of the training institutions that play a role in improving the competence of the Civil Service in the Ministry of Religion. One of the trainings held in Palembang BDK is the Distance Education and Training (DJJ). To find out about how the implementation of the Training Distance in BDK Palembang in this study were DJJ mathematics teachers Madrasah Aliyah (MA) at the Training Centre of Religious Palembang, researchers examined in depth by conducting research that aims to determine the effectiveness of the education and training distance and factor Factors that support and hinder the effectiveness of distance education and training of mathematics teachers MA in Religious Training Center Palembang. The forms of research used in this research are descriptive qualitative combined with quantitative research. The data collection techniques used were interviews, questionnaires, and documentation. The results of the overall analysis of data showed that the implementation of the Training Remote math teacher Madrasah Aliyah at the Training Centre of Religious Palembang less effective, although in terms of aspects of input demonstrate this activity is quite good, from the aspect of the implementation process and the output shows that the implementation of the Training Remote math teacher Madrasah Aliyah in Religious Training Center Palembang less effective. There are several factors that affect the implementation of the Training Remote math teacher Madrasah Aliyah Training Center Religious Palembang, which is a computer lab in the Training Centre of Religious Palembang, applicants did not meet the requirements of knowledge, especially in the control of computer/internet, and participants are often constrained in accessing to the website DJJ so they often failed to send assignments and other interactions with a tutor. In addition to inhibiting factors, there is also a contributing factor is the organizational structure of committees and a clear division of tasks, and financing of the activities from the beginning to the end of a dependent DIPA Religious Training Center Palembang. Based on the findings of the above study, it proposed several suggestions namely Training Center Religious Palembang to be able to immediately fix the computer labs that exist both in terms of infrastructure as well as the ingredients and potential participants Training Distance should prepare in advance about the knowledge of information technology and communications before they enroll as participants Training Remote so that the implementation can follow the learning process is well-meaning it can also increase the competence of teachers themselves.